2005
DOI: 10.1063/1.2049283
|View full text |Cite
|
Sign up to set email alerts
|

Quantum effects in ice Ih

Abstract: Quantum and classical simulations are carried out on ice Ih over a range of temperatures utilizing the TIP4P water model. The rigid-body centroid molecular dynamics method employed allows for the investigation of equilibrium and dynamical properties of the quantum system. The impact of quantization on the local structure, as measured by the radial and spatial distribution functions, as well as the energy is presented. The effects of quantization on the lattice vibrations, associated with the molecular translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…In future work we will use rigid-body CMD simulations to examine the temperature dependence of quantum effects in liquid water, 29 to investigate the coupling between quantization and the local structure surrounding a molecule, 30 and to explore quantum effects in ice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future work we will use rigid-body CMD simulations to examine the temperature dependence of quantum effects in liquid water, 29 to investigate the coupling between quantization and the local structure surrounding a molecule, 30 and to explore quantum effects in ice.…”
Section: Discussionmentioning
confidence: 99%
“…The analogy between quantum effects and the effects of raising the temperature was made in the early simulation studies of the structure of quantum water. 3 In a forthcoming paper 29 we will examine in detail the level to which this analogy is valid in the equilibrium and the dynamical properties of liquid water. As expected, we also found the shift associated with the softening of the potential stronger within liquid H 2 O than in D 2 O in relation to their classical counterparts.…”
Section: B Dynamical Propertiesmentioning
confidence: 99%
“…61 Many of the empirical potentials used earlier for quantum simulations of condensed phases of water treat H 2 O molecules as rigid bodies. [62][63][64] This turns out to be convenient for computational efficiency, but neglects the role of intramolecular flexibility in the structure, dynamics, and thermodynamics of the condensed water phases. 47 Moreover, the q-TIP4P/F potential takes into account the significant anharmonicity of the O-H vibration in a water molecule by considering anharmonic stretches, vs. the harmonic potentials employed in most of the simulations that considered quantum effects in these water phases.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of ice using path-integral simulations have been performed later by using mainly effective potentials, and were focused on structural and dynamic properties of several ice phases [162][163][164][165][166] . Different types of empirical potentials have been employed in these simulations [166][167][168][169][170] .…”
Section: B Icementioning
confidence: 99%
“…Gai et al 162 employed the SCP model to study ice Ih near the melting temperature, and concluded that nuclear quantum effects are appreciable at temperatures T 280 K, so that hydrogen bonds become effectively weaker. The TIP4P model was later employed to study hexagonal ice by centroid molecular dynamics 163 . The effect of quantization on the local structure, as measured by the radial and spatial distribution functions, as well as on the energy and lattice vibrational modes was presented.…”
Section: B Icementioning
confidence: 99%